The Political Constitution, the declaration of war and international law - Mezarina García, Silvio (2024)
In Article 118, paragraph 16, of the current Political Constitution of Peru, as in many of its previous political charters, the President of the Republic is granted the power to declare war and sign peace, without considering the necessity to align the national legal system with the norms of the international system. The provision that allows the President to declare war with the authorization of Congress is a legal vestige of the constitutions of the 19th century, a period in which legal recourse to war was permitted. This rule, present in the current constitutional system for a long time, has been a constant in the various constitutions that Peru has had. Since the 19th century, when resorting to war was accepted by international law, this norm has been repeated almost mechanically. However, today, it is perceived as a relic of a system that is no longer in use. In this understanding, the 1993 Constitution is not aligned with the treaties that Peru has signed and ratified. War, a legal institution that was regulated by international law, has become obsolete. There is a clear incompatibility between the Political Constitution of Peru and the international legal system, regarding the legal figure called war.